STEPS TOWARDS HARMONISING AND IMPROVING CONSUMER INSOLVENCY RULES IN THE EUROPEAN UNION - Monica CALU (Challenges of the Knowledge Society)
At various stages of the development of human society, personal insolvency has been studied in depth and analyzed in relation to various jurisdictions. Looking at the overall picture in the European Union just ahead of the implementation date of the restructuring and insolvency Directive 2019/1023/EU, most Member States had some rules on consumer insolvency. Research and evidence from these areas indicate that recourse to personal insolvency proceedings not only makes economic sense, but is also necessary to protect the fundamental rights of human beings but also the rights of consumers. However, a fundamental problem that arises in the EU is related to the ability of the various legislative frameworks in Europe to address the problem of over-indebted citizens in a more uniform way, especially since personal debts can originate in various states and can generate cross-borders issues so that certain harmonization revisions were seen as necessary. The Covid-19 crisis has added urgency to an already delayed review of these frameworks. In their efforts to mitigate the economic effects of the COVID19 pandemic on consumers, some measures introduced by Member States, although largely uncoordinated, reflect an upward trend towards harmonization and a convergence towards common approaches. This paper questions whether the personal insolvency frameworks in different Member States provide adequate answers to the personal bankruptcies induced by the COVID-19 pandemic in different European countries. Thus, the study reveals the current inadequacy of legal procedures for determining the insolvency of the debtor in various jurisdictions of the Union to the particular situations induced by the pandemic, the limitations of the current approach to the recovery of the debtor and the lack of harmonization in personal insolvency between Member States. Finally, the paper proposes steps to follow and key recommendations for an EU consumer insolvency directive.